Pengaruh Keterikatan Emosional dan Interaksi Parasosial terhadap Niat Beli Melalui Mediasi Electronic Word of Mouth - Aryanita Yunanda; Rojuaniah Rojuaniah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Hallyu phenomenon creates emotional attachment and parasocial interaction between fans and idols through social media, which brands then utilise for marketing strategies. This study aims to analyse the influence of emotional attachment and parasocial interaction on purchase intent, as well as to evaluate the mediating role of electronic word of mouth (eWOM) among K-pop fans in Indonesia. A quantitative method with an associative causal design was used through an online questionnaire using a Likert scale. The sample was obtained through purposive sampling and analysed using the Partial Least Squares – Structural Equation Modelling (PLS-SEM) method. The results of the study prove that emotional attachment and parasocial interaction have a positive influence on purchase intention, emotional attachment and parasocial interaction have a positive influence on eWOM, and eWOM has a positive influence on purchase intention. Additionally, eWOM mediates the relationship between emotional attachment and parasocial interaction on purchase intention. These findings contribute to the development of digital marketing literature and provide practical insights for brands to maximize communication strategies through public figures with strong psychological connections to their audience.